ВЫРАЖЕНИЕ ИДЕИ НАЦИОНАЛЬНОЙ НЕЗАВИСИМОСТИ В ЭПОСЕ «ЕДИГЕ» (на примере национальных версий тюркоязычных народов) - Алламбергенов, К.А. (SCIENCE and SOCIETY, 2022)
This report deals with comparative-typological analysis of the idea of national independence which is found in the national versions of the epos “Edige”.